Investigating Non-formal EFL Teachers’ Wellbeing in an English Course in Yogyakarta, Indonesia - Hapsari, Anita Galuh Sri (Language Circle: Journal of Language and Literature, 2020)
Teachers’ wellbeing potentially carries domino effects on their performances in class. Teachers develop their creativity to perform teaching and learning activities in class when they achieve wellbeing. It affects the students whether they enjoy their learning process with the teachers. This qualitative study aims to explore how the non-formal English teachers experience teaching, working dynamics and complexities from teachers’ points of view; and how these subject matters affect their wellbeing. In-depth interviews were conducted to obtain the data from the research participants. The data were analyzed by employing Holmes’s (2005) categories of teachers’ wellbeing. The findings and discussion of this research demonstrates that the teachers achieved intellectual, emotional, and spiritual wellbeing through different trajectories. The result of this study contributes to English courses as companies to maintain the teachers’ wellbeing for the sake of teachers’ performances. Future researchers are suggested to conduct similar study with quantitative approach in order to get bigger and general picture of non-formal EFL teacher wellbeing.